Dilettante or Renaissance Person? How the Order of Job Experiences Affects Hiring in an External Labor Market - Leung, Ming D. (American Sociological Review, 2014)
Social actors who move across categories are typically disadvantaged relative to their more focused peers. Yet candidates who compile experiences across disparate areas can either be appreciated as renaissance individuals or penalized as dilettantes. Extant literature has focused on the comparison between single versus multiple category members and on skill assessment, hindering its applicability. To discriminate between more versus less successful category spanners, I suggest that the order of accumulated experiences matters, because it serves as an indicator of commitment. I propose the concept of erraticism and predict that employers will prefer candidates who demonstrate some erraticism, by moving incrementally between similar jobs, over candidates who do not move and also over those with highly erratic job histories. Furthermore, I suggest this relationship holds for more complex jobs, less experienced freelancers, and is attenuated through working together. These issues are particularly salient given the rise of external labor markets where careers are increasingly marked by moves across traditional boundaries. I test and find support for these hypotheses with data from an online crowd-sourced labor market for freelancing services, Elance.com . I discuss how virtual mediated labor markets may alter hiring processes.